Promoting South Asian primary care research and projecting family medicine practitioner-scholars: A matter of critical importance - Hina Jawaid; Ramakrishna Prasad (Journal of Family Medicine and Primary Care, 2023)
South Asia, constituting India, Pakistan, Bangladesh, Nepal, Sri Lanka and Bhutan represents the most populous region in the world burdened with significant multilevel poverty. Primary care is well-documented to reduce the burden of diseases (both chronic and acute) and associated morbidity and mortality; be cost-effective and improve health outcomes and health equity for both individuals and populations. Any field, for it to stay relevant and to effectively achieve its stated mission, needs to produce its own knowledge through research. This translates into patient care, practice models, education, and advocacy for health systems strengthening and reform. In primary care, weaving experiential wisdom with clinical evidence lies at the heart of translation. In this editorial, we highlight: a) that local context, in terms of geography, community, culture, language and beliefs, influences the clinical context and practice and therefore research. Thus, relying on primary care research done elsewhere in the globe will not suffice; b) effective primary care is based on a generalist approach that involves certain ways of being, knowing, perceiving, and doing guided by the values of humility and intellectual curiosity, diversity and inclusion, equity, holistic approach to evidence, integrity, transparency, accountability and adaptability, and communication; and c) that the South Asian Region (SAR) has a number of groups experimenting and innovating with various healthcare delivery systems, much of which is not known to the larger field. The WONCA SAR Primary Care Research Network has been set up to facilitate and support scholarship, writing, and publication in primary care especially by practising family physicians. In conclusion, it will be critical to simultaneously promote grounded theory research that integrates both the family medicine/primary care perspective and the voices of families and address the ‘hidden curriculum’ that shapes the attitudes and aspirations of young doctors at both the undergraduate and postgraduate level. Family Physicians treat a variety of patients on a daily basis, in order to improve the quality of care and impact of primary care, it is imperative that the understanding and application of research is enhanced by specialists of this discipline.